Teaching Materials of Thematic Comics in the 2013 Curriculum Learning in Basic Schools - Sarkadi, Sarkadi; Alghozali, Muhammad Iqbal (Jurnal Pendidikan Indonesia, 2020)
Learning material books that are used today, especially in elementary schools (SD) are still full text, resulting in the low motivation of students to read them because they are not or not interesting. This study aims to develop thematic comics as learning materials in the 2013 Curriculum with the theme "Events in Life" and sub-theme 1 "Occupation of the Occupation of Nationality" in the fifth-grade elementary school. This research uses the Research and Development (R&D) method of the Dick and Carey model which consists of 10 stages. The study was conducted in fifth grade students in five elementary schools in Majalengka Regency. These results state that the thematic comic learning materials developed are suitable for use in the learning process in elementary school and show very good responses. The advantage of this thematic comic learning material is that it can integrate various subject matter into a theme that is presented into a story with various character characters in it. This comic learning material has an attraction for students because it is different from ordinary reading books in which it presents visualization of imaginative and colorful images.